Seeing Sesotho: art, history, and the visual language of South Sotho identity - Riep, D. M. M. (Southern African Humanities, 2013)
When approaching the topic of cultural affiliation and formation in southern Africa, the litmus test for many ethnographic studies generally stands on the work of Nicholas Jacobus van Warmelo, Government Ethnologist for South Africa (1930–1969), whose classification of African languages and ‘tribes’ essentially fixed ‘tribal’ ethnicities, and outlined the relationships of one African people to another. However, because his scholarship is largely language-based, it often presents South Sotho speakers as a homogeneous cultural entity, excluding important cultural markers such as ritual, material culture, and socio-religious beliefs. This essay offers a new methodology toward our understanding of identity by analyzing South Sotho visual arts, and their relation to oral histories and culturally sensitive activities. By examining specific examples of the arts that date from the early nineteenth century to the present, one can see that the various Sotho-speaking clans asserted themselves as heterogeneous cultural entities in spite of shared language systems, and relied on visual symbols to advance clan identity and cultural specificity. Because the visual arts are focused expressions of identity, one can gain a nuanced understanding of South Sotho affiliation and variation through the examination of objects that have been previously overlooked for the sake of locating a cohesive whole.